Technique of sacrectomy at the combined operations for locally advanced rectal cancer - Tsarkov, P.V.; Efetov, S.K.; Tulina, I.A.; Sidorova, L.V. (Rossiĭskiĭ zhurnal gastroėnterologii, gepatologii, koloproktologii, 2018)
Aim of investigation. To develop standardized technique of sacrectomy at locally advanced rectal cancer. To describe the surgical maneuvers allowing to decrease the degree of blood loss, duration of procedure and degree of surgical injury. To develop method for sacrectomy border location for the correct intraoperative navigation. Results. The distal sacrectomy technique at rectal cancer is presented in details. Abdominal-transsacral approach that includes turning patient to the prone posture for perineal stage is optimal. Small pelvis preoperative magnetic-resonance tomography with special marking may be applied for intraoperative navigation. Lateral spread of the rectal tumor requires ligation of the internal iliac arteries from abdominal approach, dissection and underrunning of the fastened veins both from abdominal and crotch access after removal of neoplastic speciemen. Conclusion. Achievement of radical degree of treatment for locally advanced rectal cancer with sacral involvement is possible only at combined operation with distal sacrectomy. Such surgical intervention is technically complex and requires special skills of pelvic operations. Technique standardization of operations, that include distal sacrectomy, could make them feasible and safe in the conditions of specialized hospital.